Insulin-like 3 affects zebrafish spermatogenic cells directly and via Sertoli cells - Diego Crespo (Nature Portfolio, 2021)
Insulin-like 3 (Insl3) belongs to a class of peptide hormones that are expressed in the Leydig cells and, in zebrafish, under the control of folliclestimulating hormone (Fsh) in the pituitary. Using insl3 knockout zebrafish, the authors found that Insl3 regulates spermatogonia differentiation and apoptosis via the Pparg and retinoic acid pathways.